Recombinase polymerase amplification - lateral flow dipstick for rapid and visual detection of Blastocystis spp. - Mei, Xuefang; Su, Changwei; Xin, Jiahui; Jia, Luwei; Zhang, Shanrui; Yang, Zhenke; Xiaowei, Tian; Zhang, Zhenchao; Wang, Shuai (Frontiers in Cellular and Infection Microbiology, 2024)
Blastocystis spp. is a ubiquitous protozoon in the intestinal tract of human and many animals. Microscopic examination is the main method of clinical diagnosis for Blastocystis spp., which is prone to false negative. A simple and rapid diagnosis of Blastocystis spp. infection is an important step to prevent and control blastocystosis. Here, a recombinase polymerase amplification-lateral flow dipstick (RPA-LFD) assay was developed for rapid visual detection of Blastocystis spp. DNA amplification could be performed within 18 min at 37°C. The minimum DNA detection limit was 1 pg/μL, and there was no cross-reactivity with 12 other non-target pathogens, which was consistent with the sensitivity of conventional PCR (cPCR). Furthermore, 56 fecal samples from the Third Affiliated Hospital of Xinxiang Medical University were tested using RPA and cPCR methods respectively, and the results were completely consistent. The results show that RPA-LFD method has high accuracy and visual results, which provides a new choice for the differential diagnosis and rapid field detection of Blastocystis spp.